Budaya Organisasi Madrasah Aliyah Negeri 1 Lamongan Sebagai Madrasah Adiwiyata Mandiri: Organizational Culture of Madrasah Aliyah Negeri 1 Lamongan as Madrasah Adiwiyata Mandiri - Victor Imaduddin Ahmad (TA'LIMUNA: Jurnal Pendidikan Islam, 2024)
This article analyzes the development of organizational culture at Madrasah Aliyah Negeri (MAN) 1 Lamongan which holds the title of Madrasah Adiwiyata. Data was obtained through observation, interviews and documentation, then analyzed descriptively qualitatively with a case study design. The findings of the article show that the organizational culture at MAN 1 Lamongan was developed through three areas: First, in the artifact area, prominent Islamic symbols are displayed, such as Islamic boarding schools, places of worship, calligraphy, Islamic posters; implementation of a curriculum that is integrated with the environment; and environmentally conscious practices, such as recycling and tree planting. Second, in the area of ​​values, promoting the values ​​of discipline, honesty, deliberation, responsibility and moderation, along with the Adiwiyata values ​​of sustainability and social responsibility. Third, in the Assumption area, all of these values ​​are based on the belief in the Islamic faith in the form of monotheism, especially in the context of actualizing the role of humans as servants of Allah and caliphs on earth. Artikel ini menganalisis pengembangan budaya organisasi pada Madrasah Aliyah Negeri (MAN) 1 Lamongan yang menyandang predikat Madrasah Adiwiyata. Data diperoleh melalui observasi, wawancara dan dokumentasi, kemudian dianalisis secara deskriptif kualitatif dengan desain studi kasus. Temuan artikel menunjukkan bahwa budaya organisasi pada MAN 1 Lamongan dikembangkan melalui tiga wilayah: Pertama, pada wilayah artefak. Ditampilkan simbol-simbol Islam yang mencolok, seperti pondok pesantren, tempat ibadah, kaligrafi, poster Islami; penerapan kurikulum yang terintegrasi dengan lingkungan; dan praktik kepedulian lingkungan, seperti daur ulang dan penanaman pohon. Kedua, pada wilayah nilai-nilai. Mempromosikan nilai-nilai kedisiplinan, jujur, musyawarah, tanggungjawab dan moderat, bersamaan dengan nilai-nilai Adiwiyata tentang keberlanjutan dan tanggung jawab sosial. Ketiga, pada wilayah Asumsi. Semua nilai-nilai tersebut dilandasi keyakinan akidah Islam berupa tauhid, terutama dalam aktualisasi peran manusia sebagai hamba Allah dan khalifah di bumi. Kata Kunci: Budaya Organisasi; Madrasah Aliyah; MAN 1 Lamongan; Madrasah Adiwiyata.